1999
DOI: 10.1093/oxfordjournals.aje.a009816
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Second Trimester Serum Tumor Necrosis Factor- -soluble Receptor p55 (sTNFp55) and Subsequent Risk of Preeclampsia

Abstract: Preeclampsia is characterized by diffuse vascular endothelial dysfunction. Tumor necrosis factor-alpha (TNF-alpha), which plays a key role in the cytokine network responsible for immunoregulation, is also known to contribute to endothelial dysfunction and other metabolic disturbances noted in preeclampsia. Results from cross-sectional studies and one longitudinal study indicate that TNF-alpha (or its soluble receptor, sTNFp55) is increased in the peripheral circulation and amniotic fluid of women with preeclam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
1
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(62 citation statements)
references
References 0 publications
4
56
1
1
Order By: Relevance
“…TNF-a is, however, also produced in adipose tissue 32 , and therefore it is essential to control for BMI. In a larger well designed study by Williams et al 33 , the circulating level of the TNF-a soluble receptor p55 was significantly increased at around 16 weeks of gestation of pre-eclamptic pregnancies. There was also a doseresponse relationship between plasma P55 and the risk of subsequent pre-eclampsia.…”
Section: Discussionmentioning
confidence: 92%
“…TNF-a is, however, also produced in adipose tissue 32 , and therefore it is essential to control for BMI. In a larger well designed study by Williams et al 33 , the circulating level of the TNF-a soluble receptor p55 was significantly increased at around 16 weeks of gestation of pre-eclamptic pregnancies. There was also a doseresponse relationship between plasma P55 and the risk of subsequent pre-eclampsia.…”
Section: Discussionmentioning
confidence: 92%
“…34 Concentrations of the soluble receptor for TNF␣ (TNF␣ receptor 1; sTNFp55) are also reportedly raised in pre-eclampsia before the clinical onset of the disease. 35,36 However, the frequency of the TNF T2 mutation in the promoter region (the only polymorphism so far studied in this context) is not increased in either pre-eclampsia or HELLP. 37 Another promising candidate gene appears to be the angiotensinogen gene.…”
Section: Geneticsmentioning
confidence: 96%
“…in preeclampsic patients when compared to normotensive controls (25,26). While certain studies report increased TNF-α or TNF-R1 levels at as early as the first trimester in patients who subsequently develop preeclampsia, others reveal no significant difference between preeclampsic patients and controls (27,28). Leal et al found that maternal serum TNF-R1 levels at 11-13 weeks gestational age was increased in pregnant subjects developing preeclampsia, but the TNF-R1 levels were not associated with the degree of impairment in placental perfusion or the severity of preeclampsia (29).…”
Section: Discussionmentioning
confidence: 96%